Karakteristik Fisis Dan Mekanis Abu Sawit (Palm Oil Fuel Ash) Dalam geoteknik - Rizqi Yuliana; Muhardi Muhardi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
POFA is an agrowaste ash which is produced from fibers, nut shells, and empty fruit bunches when burnt at temperatures of about 800-10000C in boiler. The production of POFA is rising every year, it is disposed for landfills, now become an important environmental disposal issue. A large area is required for the disposal of these POFA waste materials. The landfill of POFA is the problem for the palm oil industry when it is not reused for any work. POFA contains a large amount of silicon dioxide with high pozzolanic reactivity and has high potential to be used in any engineering work. This research examined POFA characteristics in geotechnical application and its influence by curing periods on 0, 7 and 28 days. In this paper, physical and mechanical characteristics of POFA in geotechnical work will be shown. The chemical composition of POFA prove the existence of SiO2, Al2O3, Fe2O3 and CaO as important substances supporting pozzolan reaction during cured. The result shows that the characteristic of POFA has similar behaviour with sands. Coefficient of permeability decreased during curing periods. Besides, cohesion shear strength, angle of friction, cohesion undrained, and CBR value are improve during curing periods. Keywords: POFA, geotechnic, pozzolan reaction